2019
DOI: 10.31127/tuje.503959
|View full text |Cite
|
Sign up to set email alerts
|

Closed Loop Supply Chain Management Performance Evaluation Criteria

Abstract: Evaluating chain performance to develop an effective supply chain has become a necessity because it plays a critical role in the success of businesses. The most important decision to evaluate the chain performance is the correct selection of indicators. The closed-loop supply chain method consists of a whole of forward and reverse logistics activities. For this reason, advanced supply chain management and reverse supply chain management performances are handled separately in this study. The performance evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Moreover, in the case of public organizations, the correlation between ESG indicators and financial performance is not directly and positively linked [21]. It is therefore essential to strike a balance between investment in environmental protection, social welfare and corporate governance and financial performance to ensure long-term stability [22]. Thus, it is found that ESG controversies do not have a direct effect on firm value, while the interaction seems to be very positive and significant [23].…”
Section: Literature Reviewmentioning
confidence: 95%
“…Moreover, in the case of public organizations, the correlation between ESG indicators and financial performance is not directly and positively linked [21]. It is therefore essential to strike a balance between investment in environmental protection, social welfare and corporate governance and financial performance to ensure long-term stability [22]. Thus, it is found that ESG controversies do not have a direct effect on firm value, while the interaction seems to be very positive and significant [23].…”
Section: Literature Reviewmentioning
confidence: 95%